SECURE PLACEMENT OF WEB APPLICATIONS IN CLOUD SYSTEMS AND THEIR INTEGRATION WITH CI/CD - Qurbonov Behruz Amrulloyevich; Muxtorov Maqsudbek Sherzodbek o‘g‘li (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The proliferation of cloud computing has transformed the deployment of web applications, offering scalability, flexibility, and cost-efficiency. Platforms like Amazon Web Services (AWS), Microsoft Azure, and Google Cloud Platform (GCP) provide robust infrastructure for hosting web applications. However, securing these applications in the cloud is critical due to increasing cyber threats such as data breaches, DDoS attacks, and unauthorized access. Integrating Continuous Integration/Continuous Deployment (CI/CD) pipelines enhances development efficiency but introduces additional security challenges. This article explores the methods for securely placing web applications in cloud systems and integrating them with CI/CD pipelines, addressing challenges, proposing solutions, and providing mathematical formulations and algorithms to ensure robust implementation.